Mapping The Worldwide Knowledge of Jack Bean by A Bibliometric Approach - Fitriani, Aprilia; Onyeaka, Helen; Agustia, Friska Citra (Journal of Agri-Food Science and Technology, 2024)
Indonesia's indigenous inhabitants acknowledge the local legume plant known as jack bean. The Jack bean has various advantages, including increased production, a shorter lifespan, upright stems mimicking shrubs, and improved tolerance to biotic and abiotic stresses. Nonetheless, the jack bean plant is particularly vulnerable due to harmful compounds such as canavaline, choline, hydroziamine acid, trogonelin, and cyanide. A bibliometric study was performed to locate studies on jack beans. The data collection procedure includes executing an extensive search in Scopus-indexed journals using the keywords "Jack Bean." It could limit the search to the article abstract, title, keywords, and country. The articles included in this study were published between 2000 and 2023. The search yielded a total of 999 items. The data was obtained on September 10, 2023; any later alterations are not considered in this research. According to the published literature, over the last 23 years, many studies have been conducted to develop urease inhibition and antioxidants from jack beans. However, little research has been done into the functional benefits of jack bean bioactive components for enhancing bodily health, such as antidiabetic, antihypertensive, and anticancer properties. This article contributes to helping researchers fill jack bean-related research gaps and apply technology to the industrialization process of jack beans in the functional food and nutraceutical industries.